Reprocessing of anaesthetic and ventilatory equipment - Geiss, Heinrich K. (The journal of hospital infection, 1995)
Uniform and standardized recommendations for reprocessing of anaesthetic and ventilatory equipment are still lacking. The uncertainty in this field is underscored by the various methods which are described in the literature which include pasteurization, immersion baths, formaldehyde cabinets, automated washers/disinfectors and sterilization procedures like autoclaving, ethylene oxide and gaseous formaldehyde. Based on the classification of anaesthetic and ventilatory equipment as semi-critical items, high level disinfection must be regarded as the appropriate decontamination procedure. In contrast to automated washers the other above-mentioned disinfection procedures lack an integrated and all inclusive reprocessing cycle which consists of cleaning, disinfection, rinsing and drying. In view of the increasing demands of employee safety, environmental suitability, cost-effectiveness and quality assurance in hospital hygiene, only automated washers/disinfectors—either based on hot water disinfection or chemothermic processing—fulfil the basic requirements for safe and standardized reprocessing of anaesthetic and ventilatory equipment.
Elektronische Reproduktion der Druck-Ausgabe 18. Mai 2004
Gesehen am 12.03.2025